Education for Social Change: Driving Student Success for and Beyond the Market - (:unkn) unknown (My University, 2024)
The aim of this article is to illustrate that a key strategic objective of student affairs is to contribute significantly towards student success. Education refers to the process of learning and expanding culture. It significantly contributes to the improvement of the human condition through better knowledge, health, living conditions, social equity, and productivity, and is a central tool for social progress. Student affairs practitioners and researchers are well positioned to contribute holistically to student success and as such could play a strategic role in the transformation of higher education. This article reports on a study [1] entitled ‘Towards a Qualitative Framework for Blending Equity and Excellence in Transforming South African Higher Education Transformation to Achieve Development’ in which the promotion of student success is viewed as central to institutional transformation. The purpose of the study was to contribute to a more comprehensive qualitative framework for higher education transformation in South Africa by reconciling notions of ‘equity and excellence’. The scope of the study revolves around the view of sixteen expert leaders in higher education change in South Africa. They explore elements of a qualitative framework for higher education transformation from a contemporary perspective. It answers the question as to why transformation is perceived to be so slow despite existing frameworks. Four core areas are identified as crucial to address if transformation is to be focussed and accelerated. The most crucial of these is ‘student success’. The paper presents a set of indicators that could be used to frame how transformation can occur, noting that these are to be conducted in small settings. In practice, this means that a project or site can be selected for transformation, a set of indicators developed, and a systematic approach. The researcher interviewed 16 leaders of thought in higher education transformation. Th
Keywords: African Research